The interplay between prenatal liver growth and lung development in congenital diaphragmatic hernia - Ott, Katherine C.; Bi, Michael; Scorletti, Federico; Ranginwala, Saad A.; Marriott, William S.; Peiro, Jose L.; Kline-Fath, Beth M.; Alhajjat, Amir M.; Shaaban, Aimen F. (Frontiers in Pediatrics, 2022)
Objective: Liver herniation is a known risk factor for increased severity in CDH and is associated with clinically significant pulmonary hypoplasia and pulmonary hypertension. Better studies are needed to understand the growth of the herniated liver compared to the liver that remains in the abdomen and how this liver growth then affects lung development. Serial hi-resolution fetal MRI enables characterization of liver growth throughout gestation and examination of macroscopic features that may regulate liver growth. Here, we hypothesized that the nature of liver herniation affects liver growth and, in turn, affects pulmonary development. Methods: Clinical data were retrospectively collected from consecutive cases of prenatally diagnosed isolated left-sided or right-sided CDH from June 2006 to August 2021. Only those cases with MRI lung volumetry for both mid-gestation and late-gestation time points were recruited for analysis. Cases with fetal chromosomal abnormalities and other major structural abnormalities were excluded. Fractional liver volume and liver growth was indexed to estimated fetal weight and compared to lung growth. Results: Data was collected from 28 fetuses with a left liver-down CDH (LLD), 37 left liver-up CDH (LLU) and 9 right liver-up CDH (RLU). Overall, RLU fetuses had greater overall and fractional (intra-thoracic vs intra-abdominal) liver growth when compared to LLD and LLU fetuses. Additionally, intra-thoracic liver growth was consistently slower than intra-abdominal liver growth for either right- or left-sided CDH. When the liver was not herniated, a positive correlation was seen between liver growth and lung growth. However, when the liver was herniated above the diaphragm, this positive correlation was lost and liver growth was associated with a lower lung growth. Conclusion: Right-sided CDH fetuses exhibit greater liver growth compared to left-sided CDH. Liver herniation disrupts the normal positive correlation between liver and lung growth that is seen when the liver is entirely within the abdomen.